Productivity Measures in Collective Bargaining - Barkin, Solomon (Relations industrielles / Industrial Relations, 1981)
The author examines the questions whether the measurement of productivity is a significant issue in collective bargaining and whether productivity is a primary determinant of the levels of earnings.